Reconstruction of Law in Enhancing Human Resources of the Police to Realize an Integrated Criminal Justice System - Cepi Noval; Ade Saptomo (International Journal Labs, 2024)
This research discusses the importance of improving the quality of education for Human Resources (HR) in the Indonesian National Police (Polri) to achieve effective and just law enforcement within the context of an integrated criminal justice system. Focusing on curriculum improvement, development of practice-based training methods, and the integration of Polri HR education with other actors in the criminal justice system, this study identifies strategies that can enhance the professionalism and ethics of police members. The research also analyzes the impact of improved HR education on the effectiveness of law enforcement as well as public trust in the criminal justice system. The results indicate that collaboration and harmonization among law enforcement agencies, along with strict enforcement of ethical codes, are key steps in building the integrity of Polri and creating a more democratic and trustworthy justice system.